Determination of Monomer Phenols in Cane Juice by Reversed-Phase High-Performance Liquid Chromatography with UV Detection - Liang1, Xinquan; Liang1, Xianhui; He2, Huihuan; Liu1, Jidong; Lu1, Dengjun (Asian Journal of Chemistry, 2014)
A reversed phase high-performance liquid chromatography method was used in simultaneous determination of 6 monomer phenols (e.g., gallic acid, catechin, chlorogenic acid, caffeic acid, epicatechin and ferulic acid) in cane juice. A variable wavelength UV detector and a C18 column (250 mm × 4.6 mm 5 μm) were used. The mixture of methanol, acetic acid and water were used as the mobile phase in a gradient mode. Five monomer phenols (gallic acid, chlorogenic acid, caffeic acid, epicatechin and ferulic acid) were detected in cane juice with an average recovery ratio of 81.6-93.7 % and the relative standard deviations (RSD) were less than 5 %. This method is a convenient, rapid and accurate way for simultaneous determination of monomer phenols in cane juice.